An introduction to MyBFF@school, a school-based childhood obesity intervention program: a cluster randomized controlled trial - Abdul Halim Mokhtar; Zahari Ishak; Fuziah Md. Zain; Rusidah Selamat; Abqariyah Yahya; Muhammad Yazid Jalaludin (BMC Public Health)
Abstract Obesity trend among Malaysian children is on the rise. Noting that the tendency for them to grow into obese adults and the relationship of obesity to many non-communicable diseases, the My Body is Fit and Fabulous at School (MyBFF@school program) was designed to combat obesity among the schoolchildren. The program was piloted in 2014 in Putrajaya, Malaysia. There were several challenges during the pilot study which included strain in manpower, limited variation of physical activity, nutrition, and psychology modules, time-constraint after school hours, co-curriculum marks, contamination effect, and school selection. The main MyBFF@school in 2016 addressed the challenges and improvised the design which were elaborated in subsequent articles in this supplement. This cluster randomized controlled trial was conducted in three states; Federal Territory of Kuala Lumpur, Selangor and Negeri Sembilan in 23 primary and 15 secondary schools were selected through proportionate random sampling. The MyBFF@school intervention package consisted of physical activity, nutrition and psychology components were carried out for six months. Data were collected at baseline, mid (month-3) and end (month-6) of the study period. The effects of the program on body composition, clinical, physical fitness, nutrition, and psychology were assessed in primary schoolchildren aged 9 to 11 years old (children age group) and secondary schoolchildren (adolescent) aged 13 to 16 years old. The prevalence of overweight and obesity at screening (N=22,816) were 29.4% in primary and 26.8% in secondary schoolchildren. Outcomes of the trial is presented in this supplement. In summary, the MyBFF@school program is a school-based intervention for overweight and obese children and adolescent. It is a combination of physical activity, nutrition and psychology components. We present in this supplement, the rationale, methodology and the outcomes of this randomized control trial of the MyBFF@school program.